Análise da substituição parcial da areia por pó de rocha calcária no concreto - Bezerra, Leardo Simplicio (Universidade Federal Rural do Semi-Árido, 2019)
The production of granitic and limestone rocks generates a large amount of waste, being accumulated in large stocks and often inadequately, causing considerable environmental impacts. In addition, these wastes have properties that can bring benefits to the quality of products such as concrete and mortars. In addition, the construction industry consumes a large amount of natural sand to compose these products, generating damages to the environment and reducing the sources of this resource. Thus, the addition of limestone rock crusher to the partial replacement of the sand is a good solution to reduce these impacts and ensure sustainability. Therefore, substitutions of 10%, 20%, 30%, 40% and 50% were carried out, maintaining the desired consistency and workability. Moreover, the specimens were submitted to axial compression and diametral compression (traction), obtaining results with better performance and others with worse. Those that presented inferior results to those of concrete specimens with no percentage of residue, may be acceptable depending on the requests foreseen in the project.
Monografia
Keywords: Resíduos de rocha calcária; Areia natural.; Impactos ambientais.; Concreto; Sustentabilidade; Limestone rock waste; Natural sand; Concrete; Environmental Impacts; Sustainability; ENGENHARIAS::ENGENHARIA CIVIL